KEPEMIMPINAN PEREMPUAN DALAM PERSPEKTIF AL-QUR’AN - Siti Fatimah (LPPM Institut Agama Islam Al-Hikmah Tuban, 2015)
Speaking of leadership, particularly concerning Islamic leadership is an issue that is very interesting to study. Because from a good leadership system, there will be a good order of society as well.In Indonesia the majority of the population is Muslim, but admitted or not, from the beginning until now the implementation of democracy that is also part of the teachings of Islam, has still been quite alarming. This can be seen from the inequality of the social position of women. Since 14 centuries ago, the Qur'an has abolished a wide range of discrimination between men and women, the Qur'an gives rights to women as well as the rights granted to men. In this case is the issue of Islamic leadership in which Islam has given rights to women as that given to men. In addition, Islam has also impose obligations to women as that imposed to men, except the rights or obligations devoted by Islam to men.